1993
DOI: 10.1143/jjap.32.4144
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Pb(Zr, Ti)O3 Films on Pt/Ti/Ta Electrodes by Sol-Gel Process

Abstract: Tl 2 Ba 2 Ca 1 Cu 2 O x thin films on (001) LaAlO 3 with excellent alignment suitable for microwave applications at 77 K have been fabricated using an ex situ anneal step in argon atmospheres at temperatures of 720-740 • C. Surface resistance values as low as 400 µ (79 K, 10 GHz) and large-area critical current densities up to 3.4 × 10 5 A cm −2 (77 K) have been achieved. In order to understand the relationship between the microstructure and electrical properties the films have been characterized by a variety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…39,40) Several authors suggested that Ti (or TiO x ) affects the nucleation of the PZT layer and its orientation. 27,[41][42][43][44][45][46][47][48] We measured the temporal changes in XRD intensity during the PLZT-PDA of PLZT {111}, PLZT {100}, PLZT {110}, and pyro {222} from specimen B (PLZT on Pt=Ti in Table I) with Pt-PDA (data not shown). The PPT speed of specimen B with Pt-PDA was higher than that of specimen A without Pt-PDA.…”
Section: Resultsmentioning
confidence: 99%
“…39,40) Several authors suggested that Ti (or TiO x ) affects the nucleation of the PZT layer and its orientation. 27,[41][42][43][44][45][46][47][48] We measured the temporal changes in XRD intensity during the PLZT-PDA of PLZT {111}, PLZT {100}, PLZT {110}, and pyro {222} from specimen B (PLZT on Pt=Ti in Table I) with Pt-PDA (data not shown). The PPT speed of specimen B with Pt-PDA was higher than that of specimen A without Pt-PDA.…”
Section: Resultsmentioning
confidence: 99%